P1425Complication rate and incidence of esophageal injury after minimally invasive convergent procedure for treatment of atrial fibrillation. (18th June 2020) - Prolic Kalinsek, T; Gersak, B; Jan, M
Abstract: Funding Acknowledgements: None Introduction: Convergent procedure is a minimally invasive surgical approach for treatment of atrial fibrillation (AF) combining epicardial and endocardial radiofrequency (RF) ablation. However, there is conflicting data regarding the rate of major complications after convergent treatment of AF. Apart from common complications the esophageal injury incidence after convergent procedure is not well documented. Purpose: Our aim was to assess major complication occurrence after convergent procedure with additional emphasis on the incidence of esophageal injury. Methods: One hundred forty-seven consecutive patients (113 male, mean age 59 ± 9 years, BMI 29 ± 5 kg/m2) with persistent (122, 83%) and paroxysmal (25, 17%) AF were treated with convergent procedure that included epicardial RF ablation with coagulation devices (12 lesions, each for 90 s, with 30 W power), combined with endocardial RF catheter ablation for pulmonary vein isolation. The approach for epicardial ablation was diaphragmatic pericardial window through subxiphoid incision. Infusion of cooled saline into the pericardial space during epicardial ablations and monitoring of esophageal temperature with temperature probe were additional precautions to avoid esophageal overheating. All patients had endoscopy of the esophagus at least 2 days after the procedure to assess for presence of esophageal injury. Adverse events resulting in additional intervention or causing long-term disability were defined as major complication. Results: During short-term follow-up (minimum of 5 months) major complication rate was 6.1%. Three patients had cardiac tamponade, 4 had abdominal bleeding, 1 had ischemic stroke and 1 had arterial pseudoaneurysm. Esophageal mucosal lesions were observed in 11 patients (7.5%) that did not result in major complication. All lesions were followed with additional endoscopies and resolved without any intervention. Conclusions: Complication rate after minimally invasive convergent procedure for treatment of AF in our patient cohort is low. Prevention of esophageal overheating resulted in absence of major esophageal injury.